Viral encephalopathy and retinopathy is endemic in wild groupers (genus Epinephelus spp.) of the Algerian coast. Issue 7 (27th May 2020) - Boukedjouta, Rachid; Pretto, Tobia; Abbadi, Miriam; Biasini, Lorena; Toffan, Anna; Mezali, Karim
Abstract: This work describes betanodavirus infection in two species of groupers (family Serranidae) from the Algerian coast: the dusky grouper Epinephelus marginatus and the golden grouper Epinephelus costae . At necropsy, characteristic clinical signs, external injuries, clouded eyes and brain congestion, generally associated with viral encephalopathy and retinopathy (VER) infection were observed. The partial sequences of RNA1 and RNA2 from two viral strains were obtained, and the phylogenetic analysis revealed the presence of the red‐spotted grouper nervous necrosis virus (RGNNV) genotype closely related to strains previously detected in groupers in the same geographic area. Results obtained in this study support the hypothesis that VER disease is endemic in the Algerian grouper population.